Design and Construction of a New Automated Device for Testing the Scratch Resistance of Polymeric Materials - Hussein, Mushtaq Abdul Kareem; Hassan, Abdul Kareem F.; Saad, Najim Abdul Ameer (Basrah Journal for Engineering Sciences, 2020)
This study focuses on the design and construction of an automated device for evaluating the scratch resistance of polymeric materials by measuring the force required to produce surface scratches and calculating the corresponding friction coefficient from device input–output data. The device was fabricated using locally available materials, with several components manufactured in local mechanical workshops. It comprises four main subsystems: mechanical components, scratching mechanism, electrical and electronic units, and an operating control program. The developed device offers the following specifications: normal load range of 0.1–325 N, sliding speed of 1–35 mm/s, tangential force measurement capacity of 0.1–294 N via a load cell, sample dimensions of 10–195 mm in length, 10–125 mm in width, and 0.25–50 mm in thickness, a maximum scratch length of 195 mm, and an adjustable indenter height ranging from 0.25 to 50 mm above the platform surface. Scratch testing and friction coefficient measurements were conducted on pure PMMA and PMMA reinforced with silicon dioxide (SiO₂) nanoparticles. Experimental results demonstrated increased scratch resistance and reduced friction coefficients with higher SiO₂ weight ratios. Additionally, the performance evaluation confirmed that the designed device is capable of accurately and rapidly measuring the tangential forces associated with scratching through a simple operational procedure.